Nghiên cứu tổng hợp biodiesel từ dầu ăn phế thải trên xúc tác dị thể MgSiO3. - Sơn, Nguyễn Trung; Thuý, Đỗ Thị Diễm; Ngọ, Đinh Thị (Vietnam Journal of Chemistry, 2012)
Currently, biodiesel was manufactured mainly from edible oils having high price, on homogeneous catalysts, un-regeneration, difficult separation, lesser effective economics and polluted environment. Therefore, the cheap new raw material such as waste oil and heterogeneous catalysts has been found to get over the above disadvantages. On advance works gived out methods of waste oil treatment. This news, searched to synthesize biodiesel from waste oil treated, on catalysis MgSiO3.